Gestión de talento humano y su impacto en el desempeño del personal de la hacienda agrícola marinita cia. ltda., año 2023 - Castro Sánchez, Johnny Javier (2024)
The objective of this research is to evaluate the management of human talent and its impact on the performance of the staff of the Hacienda Agrícola Marinita Cía. Ltda. In today's business environment, characterized by increasing competition and dynamism, effective human talent management is essential for organizational success. The research methodology combined a mixed approach, using qualitative and quantitative elements. Interviews were conducted with the administrative manager and the person responsible for human talent management, and all company personnel were surveyed. The surveys used a 5-point Likert scale and simple “Yes” and “No” questions. The collected data were tabulated in Excel and analyzed with SPSS V25 statistical software. The results indicate that there is a lack of functional manuals, procedures and indicators to evaluate talent management processes, which generates work overload and lack of internal communication. In addition, areas for improvement were identified in the induction, training and delivery of the internal work regulations, leaving 71% of the staff confused. Although 91% of employees consider that the work environment is good, this is due to the adequate provision of materials and equipment necessary for their activities. In terms of workforce growth, absences and workplace accidents, the results reflect the effectiveness of talent management.